A weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover and its manufacturing process
By adding polyurethane modified vapor-phase silica to the glue of the epoxy glass fiber semi-cured sheet, the problem of floating hollow glass microbeads is solved, the dispersion and thickness uniformity are improved, and the lightweight, high strength and high toughness of the epoxy glass fiber fabric semi-cured sheet is achieved.
Patent Information
- Application Number
- CN202411904838.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
When using hollow glass microbeads in existing epoxy fiber semi-cured sheets, hollow glass microbeads are prone to float on the surface of the glue, resulting in uneven dispersion, affecting the uniformity of the thickness and the thickness pass rate of the product.
Polyurethane-modified gas-phase silica is used to pretreat and modify the gas-phase silica with a silane coupling agent to enhance its interface bonding force with epoxy resin and waterproof stability, thereby improving the dispersion of hollow glass microbeads.
It effectively improves the thickness uniformity and thickness pass rate of the epoxy fiber cloth semi-cured sheet, reduces the weight of the product, and improves its strength and toughness.
Smart Images

Figure BDA0005204146870000081 
Figure BDA0005204146870000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of electronic product housing technology, and in particular to a weight-reducing epoxy glass fiber cloth semi-cured sheet for a mobile phone back cover and a manufacturing process thereof. Background Art
[0002] As mobile phones become thinner and lighter, the back covers of mobile phones have been transformed from the original glass and composite panels to epoxy glass fiber semi-cured sheets formed by hot pressing. Due to the good strength of epoxy glass fiber, the product thickness can be reduced by 2 times compared with the original material thickness, and the weight can be reduced by more than half.
[0003] The density of epoxy glass fiber is 1.9-2.0g / cm 3 The density is relatively high and has a certain weight. In order to further reduce the weight, most people add a certain proportion of hollow glass beads to the epoxy glue, and the density of the prepreg can be reduced to 1.2-1.4g / cm 3 , the weight of the product can be reduced by 1 / 3; however, due to the low density and smooth surface of the hollow glass beads, they are easy to float on the glue during the gluing process of the prepreg. In this way, the glass beads are unevenly dispersed on the prepreg, resulting in uneven thickness of the prepreg, which has a great impact on the qualified rate of product thickness, and the product weight is also uneven. Summary of the invention
[0004] In order to improve the problem that hollow glass microspheres are easy to float and further reduce the weight of epoxy glass fiber semi-cured sheets, the present application provides a weight-reducing epoxy glass fiber cloth semi-cured sheet for mobile phone back covers and a manufacturing process thereof.
[0005] The present application provides a weight-reducing epoxy glass fiber cloth prepreg for a mobile phone back cover and a manufacturing process thereof, which adopts the following technical solutions: A weight-reducing epoxy glass fiber cloth prepreg for a mobile phone back cover, the epoxy glass fiber cloth prepreg comprising glass fiber cloth and glue; the glue raw materials comprise, by weight percentage, 40-45% of epoxy resin, 1-2% of curing agent, 0.1-0.5% of dispersant, 25.5-45.9% of solvent, 10-18% of hollow glass microspheres, and 3-9% of modified fumed silica; the modified fumed silica is polyurethane-modified fumed silica.
[0006] By adopting the above technical scheme, the particle size of the fumed silica is small, the specific surface area is large, the surface adsorption capacity is strong, and the surface energy is large. When a certain proportion of fumed silica and dispersant are added to the glue formula, the viscosity of the glue increases and the hollow glass microspheres are not easy to float. The most important thing is that the fumed silica can be adsorbed on the surface of the hollow microspheres, and the hollow glass microspheres do not float on the surface of the glue. The present application adopts polyurethane-modified fumed silica. Due to the introduction of polyurethane chain segments, the interfacial bonding force and waterproof stability of the fumed silica and the epoxy resin are effectively enhanced, thereby further improving the dispersibility of the hollow glass microspheres in the epoxy glass fiber cloth, effectively improving the uniform stability of the thickness of the epoxy glass fiber cloth semi-cured sheet, and improving the thickness qualification rate of the product.
[0007] Preferably, the polyurethane modified fumed silica is prepared from the following raw materials: polytetramethylene ether glycol, pretreated fumed silica, and 4,4′-diphenylmethane diisocyanate, and the weight ratio of the three is 100:(4-6):(40-80). Preferably, the pretreated fumed silica is prepared from the following raw materials in parts by weight: 10-20 parts of fumed silica, 2-4 parts of silane coupling agent, and 98-196 parts of anhydrous ethanol.
[0008] By adopting the above technical scheme, the fumed silica is pretreated and modified with a silane coupling agent, so that the hydrophobicity of the fumed silica can be improved, so that the fumed silica can be evenly dispersed in the polyurethane prepolymer, thereby effectively improving the modification effect, further improving the mechanical properties of the product, and obtaining a modified fumed silica with light weight, high strength and good toughness.
[0009] Preferably, the method for preparing the pretreated fumed silica comprises the following steps: The fumed silica is placed at 100-130°C for drying for 2-4 hours and then used for later use; the silane coupling agent is dissolved in anhydrous ethanol to obtain a silane coupling agent solution, and the solution is stirred and dispersed for 10-20 minutes; the dried fumed silica is added, mixed evenly, and ultrasonically dispersed at room temperature for 30-40 minutes, and then heated to 80-90°C for reaction for 10-12 hours; after the reaction is completed, vacuum filtration is performed, and the pretreated fumed silica is obtained after drying.
[0010] Preferably, the method for preparing the polyurethane-modified fumed silica comprises the following steps: After vacuum dehydration of polytetramethylene ether glycol at 105-115°C for 2-3h, add pretreated fumed silica and stir evenly. After cooling to room temperature, add 4,4′-diphenylmethane diisocyanate. After heating to 80-90°C, react for 2-3h under nitrogen protection. After the reaction is completed, cure in an oven for 12-16h and cool for 24-48h to obtain polyurethane modified fumed silica.
[0011] Preferably, the epoxy resin is one or a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin.
[0012] By adopting the above technical solution, bisphenol A epoxy resin and bisphenol F epoxy resin have good bonding strength and thermal stability, and good fiber impregnation, which helps the glue to better penetrate into the fiber structure of the semi-cured sheet and improve the overall strength and durability of the product.
[0013] Preferably, the curing agent is one or a mixture of pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl), hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride.
[0014] Preferably, the dispersant is an anionic dispersant.
[0015] By adopting the above technical solution, the anionic dispersant carries a negative charge and has an anionic group in its molecular structure. In the epoxy resin glue, it can form a charge repulsion effect with the resin particles, so that the resin particles and hollow glass microspheres form a stable dispersion system in the glue, effectively improving the dispersibility.
[0016] The present application provides a manufacturing process for a weight-reducing epoxy glass fiber cloth prepreg for a mobile phone back cover, which adopts the following technical solution: A manufacturing process for a weight-reducing epoxy glass fiber cloth prepreg for a mobile phone back cover comprises the following steps: S1. The solvent and curing agent are mixed evenly, and then epoxy resin and dispersant are added. After mixing evenly, hollow glass beads are added under stirring, and stirring is continued for 3-5 hours. Modified fumed silica is added and stirred for 2-5 hours to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake for 3-6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0017] Preferably, the baking temperature is 60-100°C.
[0018] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application adopts polyurethane modified fumed silica. Due to the introduction of polyurethane chain segments, the interfacial bonding strength and waterproof stability between fumed silica and epoxy resin are effectively enhanced, thereby further improving the dispersibility of hollow glass microspheres in epoxy glass fiber cloth, effectively improving the uniform stability of the thickness of the epoxy glass fiber cloth semi-cured sheet, and improving the thickness qualification rate of the product; 2. The fumed silica is pretreated and modified with a silane coupling agent to improve the hydrophobicity of the fumed silica, so that the fumed silica can be evenly dispersed in the polyurethane prepolymer, thereby effectively improving the modification effect, further improving the mechanical properties of the product, and obtaining a modified fumed silica with light weight, high strength and good toughness. DETAILED DESCRIPTION
[0019] The present application is further described in detail below with reference to the embodiments.
[0020] Preparation Example Preparation Example 1 S1. Dry the fumed silica at 100°C for 4 hours and set aside; dissolve 2g of silane coupling agent KH-550 in 98g of anhydrous ethanol to obtain a silane coupling agent solution, and stir and disperse for 10 minutes; add 10g of the dried fumed silica, mix well, and perform ultrasonic dispersion treatment at room temperature and 21kHz for 30 minutes, then heat to 80°C and react for 10 hours; after the reaction is completed, vacuum filter and dry to obtain pretreated fumed silica; S2. After vacuum dehydrating 100g of polytetramethylene ether glycol at 105°C for 2h, add 4g of pretreated fumed silica obtained in S1 and stir evenly. After cooling to room temperature, add 40g of 4,4′-diphenylmethane diisocyanate. After heating to 80°C, react for 2h under nitrogen protection. After the reaction is completed, cure in an oven for 12h. After cooling for 24h, polyurethane-modified fumed silica is obtained.
[0021] Preparation Example 2 S1. Dry the fumed silica at 100°C for 4 hours and set aside; dissolve 2g of silane coupling agent KH-550 in 98g of anhydrous ethanol to obtain a silane coupling agent solution, and stir and disperse for 10 minutes; add 10g of the dried fumed silica, mix well, and perform ultrasonic dispersion treatment at room temperature and 21kHz for 30 minutes, then heat to 80°C and react for 10 hours; after the reaction is completed, vacuum filter and dry to obtain pretreated fumed silica; S2. After vacuum dehydrating 100g of polytetramethylene ether glycol at 105°C for 2h, add 5g of pretreated fumed silica obtained in S1 and stir evenly. After cooling to room temperature, add 60g of 4,4′-diphenylmethane diisocyanate. After heating to 80°C, react for 2h under nitrogen protection. After the reaction is completed, cure in an oven for 12h. After cooling for 24h, polyurethane-modified fumed silica is obtained.
[0022] Preparation Example 3 S1. Dry the fumed silica at 100°C for 4 hours and set aside; dissolve 2g of silane coupling agent KH-550 in 98g of anhydrous ethanol to obtain a silane coupling agent solution, and stir and disperse for 10 minutes; add 10g of the dried fumed silica, mix well, and perform ultrasonic dispersion treatment at room temperature and 21kHz for 30 minutes, then heat to 80°C and react for 10 hours; after the reaction is completed, vacuum filter and dry to obtain pretreated fumed silica; S2. After vacuum dehydrating 100g of polytetramethylene ether glycol at 105°C for 2h, add 6g of pretreated fumed silica obtained in S1 and stir evenly. After cooling to room temperature, add 80g of 4,4′-diphenylmethane diisocyanate, heat to 80°C, and react for 2h under nitrogen protection. After the reaction is completed, cure in an oven for 12h. After cooling for 24h, polyurethane-modified fumed silica is obtained.
[0023] Preparation Example 4 S1. Dry the fumed silica at 100°C for 4 hours and set aside; dissolve 2g of silane coupling agent KH-550 in 98g of anhydrous ethanol to obtain a silane coupling agent solution, and stir and disperse for 10 minutes; add 10g of the dried fumed silica, mix well, and perform ultrasonic dispersion treatment at room temperature and 21kHz for 30 minutes, then heat to 80°C and react for 10 hours; after the reaction is completed, vacuum filter and dry to obtain pretreated fumed silica; S2. After vacuum dehydrating 100g of polytetramethylene ether glycol at 105°C for 2h, add 2g of pretreated fumed silica obtained in S1 and stir evenly. After cooling to room temperature, add 20g of 4,4′-diphenylmethane diisocyanate. After heating to 80°C, react for 2h under nitrogen protection. After the reaction is completed, cure in an oven for 12h. After cooling for 24h, polyurethane-modified fumed silica is obtained.
[0024] Preparation Example 5 S1. Dry the fumed silica at 100°C for 4 hours and set aside; dissolve 2g of silane coupling agent KH-550 in 98g of anhydrous ethanol to obtain a silane coupling agent solution, and stir and disperse for 10 minutes; add 10g of the dried fumed silica, mix well, and perform ultrasonic dispersion treatment at room temperature and 21kHz for 30 minutes, then heat to 80°C and react for 10 hours; after the reaction is completed, vacuum filter and dry to obtain pretreated fumed silica; S2. After vacuum dehydrating 100g of polytetramethylene ether glycol at 105°C for 2h, add 2g of pretreated fumed silica obtained in S1 and stir evenly. After cooling to room temperature, add 100g of 4,4′-diphenylmethane diisocyanate. After heating to 80°C, react for 2h under nitrogen protection. After the reaction is completed, cure in an oven for 12h. After cooling for 24h, polyurethane-modified fumed silica is obtained.
[0025] Preparation Example 6 S1. Dry the fumed silica at 115°C for 3 hours and set aside; dissolve 3g of silane coupling agent KH-550 in 147g of anhydrous ethanol to obtain a silane coupling agent solution, and stir and disperse for 15 minutes; add 15g of dried fumed silica, mix well, and ultrasonically disperse at room temperature and 21kHz for 35 minutes, then heat to 85°C and react for 11 hours; after the reaction, vacuum filter and dry to obtain pretreated fumed silica; S2. After vacuum dehydrating 100g of polytetramethylene ether glycol at 110°C for 2.5h, add 4g of pretreated fumed silica obtained in S1 and stir evenly. After cooling to room temperature, add 40g of 4,4′-diphenylmethane diisocyanate, heat to 85°C, and react for 2.5h under nitrogen protection. After the reaction is completed, cure in an oven for 14h and cool for 36h to obtain polyurethane-modified fumed silica.
[0026] Preparation Example 7 S1. Dry the fumed silica at 130°C for 2h and set aside; dissolve 4g of silane coupling agent KH-550 in 196g of anhydrous ethanol to obtain a silane coupling agent solution, and stir and disperse for 20min; add 20g of the dried fumed silica, mix well, and ultrasonically disperse at room temperature and 21kHz for 40min, then heat to 90°C and react for 12h; after the reaction, vacuum filter and dry to obtain pretreated fumed silica; S2. After vacuum dehydrating 100g of polytetramethylene ether glycol at 115°C for 3h, add 4g of pretreated fumed silica obtained in S1 and stir evenly. After cooling to room temperature, add 40g of 4,4′-diphenylmethane diisocyanate. After heating to 90°C, react for 3h under nitrogen protection. After the reaction is completed, cure in an oven for 16h. After cooling for 48h, polyurethane-modified fumed silica is obtained. Example
[0027] Example 1 S1. 45.9 kg of solvent water and 1 kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 40 kg of bisphenol A epoxy resin and 0.1 kg of dispersant sodium oleate were added. After mixing evenly, 10 kg of hollow glass microspheres were added under stirring, and stirring was continued for 3 h. Then, 3 kg of modified fumed silica prepared in Preparation Example 1 was added, and stirred for 2 h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 60°C for 6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0028] Example 2 S1. 35.7kg of solvent water and 1.5kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 42.5kg of bisphenol A epoxy resin and 0.3kg of dispersant sodium oleate were added. After mixing evenly, 14kg of hollow glass microspheres were added under stirring, and stirring was continued for 3h. Then, 6kg of modified fumed silica prepared in Preparation Example 1 was added, and stirred for 2h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 60°C for 6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0029] Example 3 S1. 25.5kg of solvent water and 2kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 45kg of bisphenol A epoxy resin and 0.5kg of dispersant sodium oleate were added. After mixing evenly, 18kg of hollow glass microspheres were added under stirring, and stirring was continued for 3h. Then, 9kg of modified fumed silica prepared in Preparation Example 1 was added, and stirred for 2h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 60°C for 6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0030] Example 4 S1. 45.9 kg of solvent water and 1 kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 40 kg of bisphenol A epoxy resin and 0.1 kg of dispersant sodium oleate were added. After mixing evenly, 10 kg of hollow glass microspheres were added under stirring, and stirring was continued for 4 h. Then, 3 kg of modified fumed silica prepared in Preparation Example 1 was added, and stirred for 3.5 h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 80°C for 5 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0031] Example 5 S1. 45.9 kg of solvent water and 1 kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 40 kg of bisphenol A epoxy resin and 0.1 kg of dispersant sodium oleate were added. After mixing evenly, 10 kg of hollow glass microspheres were added under stirring, and stirring was continued for 5 h. Then, 3 kg of modified fumed silica prepared in Preparation Example 1 was added, and stirred for 5 h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 100°C for 3 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0032] Example 6 The difference between Example 6 and Example 1 is that the epoxy resin used in Example 6 is bisphenol F epoxy resin.
[0033] Example 7 The difference between Example 7 and Example 1 is that the epoxy resin used in Example 7 is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, and the mass ratio of the two is 1:1.
[0034] Example 8 The difference between Example 8 and Example 1 is that the curing agent used in Example 8 is hexahydrophthalic anhydride.
[0035] Example 9 The difference between Example 9 and Example 1 is that the curing agent used in Example 9 is a mixture of methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride and 1,3,5-tris(3-mercaptobutyryloxyethyl), and the mass ratio of the two is 1:1.
[0036] Example 10 The difference between Example 10 and Example 1 is that the modified fumed silica used in Example 10 is prepared by Preparation Example 2.
[0037] Embodiment 11 The difference between Example 11 and Example 1 is that the modified fumed silica used in Example 11 is prepared by Preparation Example 3.
[0038] Example 12 The difference between Example 12 and Example 1 is that the modified fumed silica used in Example 12 is prepared by Preparation Example 4.
[0039] Embodiment 13 The difference between Example 13 and Example 1 is that the modified fumed silica used in Example 13 is prepared by Preparation Example 5.
[0040] Embodiment 14 The difference between Example 14 and Example 1 is that the modified fumed silica used in Example 14 is prepared by Preparation Example 6.
[0041] Embodiment 15 The difference between Example 15 and Example 1 is that the modified fumed silica used in Example 15 is prepared by Preparation Example 7.
[0042] Comparative Example Comparative Example 1 S1. 52.9 kg of solvent water and 1 kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 40 kg of bisphenol A epoxy resin and 0.1 kg of dispersant sodium oleate were added. After mixing evenly, 5 kg of hollow glass microspheres were added under stirring, and stirring was continued for 3 h. Then, 1 kg of modified fumed silica prepared in Preparation Example 1 was added, and stirred for 2 h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 60°C for 6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0043] Comparative Example 2 S1. 18.5kg of solvent water and 2kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 45kg of bisphenol A epoxy resin and 0.5kg of dispersant sodium oleate were added. After mixing evenly, 22kg of hollow glass microspheres were added under stirring, and stirring was continued for 3h. Then, 12kg of modified fumed silica prepared in Preparation Example 1 was added, and stirred for 2h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 60°C for 6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0044] Comparative Example 3 S1. 48.9kg of solvent water and 1kg of curing agent pentaerythritol tetrakis (3-mercaptobutyrate) were mixed evenly, and then 40kg of bisphenol A epoxy resin and 0.1kg of dispersant sodium oleate were added. After mixing evenly, 10kg of hollow glass microspheres were added under stirring, and stirring was continued for 3h to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake at 60°C for 6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
[0045] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the material used in Comparative Example 4 is ordinary fumed silica that has not been modified.
[0046] Performance testing 1. The tensile strength of the epoxy glass fiber cloth prepregs obtained in Examples 1-15 and Comparative Examples 1-4 was tested with reference to GB / T 2567 "Test Methods for Properties of Resin Castings". The results are shown in Table 1. 2. The density of the epoxy glass fiber cloth prepregs obtained in Examples 1-15 and Comparative Examples 1-4 was tested, and the results are shown in Table 1; 3. Six epoxy glass fiber cloth prepregs were taken and heated at a pressure of 40 kgf / cm 2 The temperature was 150° C. and hot pressed for 5 minutes to obtain an epoxy glass fiber cloth board. The molding thickness thereof was measured to see whether it reached the molding thickness of 0.6±0.02 mm. 20 groups were tested for each embodiment and comparative example, and the thickness qualification rate was calculated. The results are shown in Table 1.
[0047] The specific test results are as follows: Table 1 Performance test results It can be seen from the test results in Table 1 that the epoxy glass fiber cloth prepreg provided by the present application for weight reduction of mobile phone back cover has high tensile strength and a density of 1.2-1.4 g / cm 3 , which can effectively reduce the weight of epoxy glass fiber cloth semi-cured sheet; the thickness of the epoxy glass fiber board obtained by stacking 6 layers is 0.6±0.02㎜, and the thickness qualification rate is relatively high.
[0048] It can be seen from the test results of Examples 1-5 and Comparative Examples 1-4 that the epoxy glass fiber cloth prepreg provided by the present application for weight reduction of mobile phone back cover can effectively reduce the strength and quality of the epoxy glass fiber cloth prepreg and improve the thickness qualification rate of epoxy glass fiber board products. When modified fumed silica is not used in the raw materials, the strength of the obtained epoxy glass fiber cloth prepreg is significantly reduced, the density is increased, and the qualification rate is significantly reduced; when ordinary unmodified fumed silica is used, the strength of the obtained epoxy glass fiber cloth prepreg is also significantly reduced, the density is increased, and the qualification rate is reduced.
[0049] It can be seen from the test results of Example 1 and Examples 10-15 that the raw materials and preparation method of polyurethane-modified fumed silica provided in the present application, and the obtained modified fumed silica can effectively reduce the strength and quality of epoxy glass fiber cloth semi-cured sheets and improve the thickness qualification rate of epoxy glass fiber board products.
[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover, characterized by: The epoxy glass fiber cloth semi-cured sheet comprises glass fiber cloth and glue; the glue raw materials comprise 40-45% epoxy resin, 1-2% curing agent, 0.1-0.5% dispersant, 25.5-45.9% solvent, 10-18% hollow glass microspheres, and 3-9% modified fumed silica by weight percentage; the modified fumed silica is polyurethane modified fumed silica.
2. The weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 1, characterized in that: The polyurethane modified fumed silica is prepared from the following raw materials: polytetramethylene ether glycol, pretreated fumed silica and 4,4'-diphenylmethane-diisocyanate, wherein the weight ratio of the three is 100:(4-6):(40-80).
3. The weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 2, characterized in that: The pretreated fumed silica is prepared from the following raw materials in parts by weight: 10-20 parts of fumed silica, 2-4 parts of silane coupling agent, and 98-196 parts of anhydrous ethanol.
4. The weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 3, characterized in that: The method for preparing the pretreated fumed silica comprises the following steps: The fumed silica is placed at 100-130°C for drying for 2-4 hours and then used for later use; the silane coupling agent is dissolved in anhydrous ethanol to obtain a silane coupling agent solution, and the solution is stirred and dispersed for 10-20 minutes; the dried fumed silica is added, mixed evenly, and ultrasonically dispersed at room temperature for 30-40 minutes, and then heated to 80-90°C for reaction for 10-12 hours; after the reaction is completed, vacuum filtration is performed, and the pretreated fumed silica is obtained after drying.
5. The weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 2, characterized in that: The preparation method of the polyurethane modified fumed silica comprises the following steps: After vacuum dehydration of polytetramethylene ether glycol at 105-115°C for 2-3h, add pretreated fumed silica and stir evenly. After cooling to room temperature, add 4,4′-diphenylmethane diisocyanate. After heating to 80-90°C, react for 2-3h under nitrogen protection. After the reaction is completed, cure in an oven for 12-16h and cool for 24-48h to obtain polyurethane modified fumed silica.
6. The weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 1, characterized in that: The epoxy resin is one of bisphenol A epoxy resin and bisphenol F epoxy resin or a mixture of the two.
7. The weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 1, characterized in that: The curing agent is one of pentaerythritol tetrakis (3-mercaptobutyrate), 1,3,5-tris (3-mercaptobutyryloxyethyl), hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride, or a mixture of several of them.
8. The weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 1, characterized in that: The dispersant is an anionic dispersant.
9. A process for producing a weight-reducing epoxy glass fiber cloth prepreg for a mobile phone back cover according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. The solvent and curing agent are mixed evenly, and then epoxy resin and dispersant are added. After mixing evenly, hollow glass beads are added under stirring, and stirring is continued for 3-5 hours. Modified fumed silica is added and stirred for 2-5 hours to obtain glue; S2. Soak the glass fiber cloth in the glue obtained in S1, scrape the glue, bake for 3-6 minutes, and obtain the epoxy glass fiber cloth semi-cured sheet after cooling.
10. The manufacturing process of the weight-reducing epoxy glass fiber cloth prepreg for mobile phone back cover according to claim 9, characterized in that: The baking temperature is 60-100°C.